Variation in the prion protein sequence in Dutch goat breeds. (14th March 2016) - Windig, J.J.; Hoving, R.A.H.; Priem, J.; Bossers, A.; van Keulen, L.J.M.; Langeveld, J.P.M.
Summary: Scrapie is a neurodegenerative disease occurring in goats and sheep. Several haplotypes of the prion protein increase resistance to scrapie infection and may be used in selective breeding to help eradicate scrapie. In this study, frequencies of the allelic variants of the PrP gene are determined for six goat breeds in the Netherlands. Overall frequencies in Dutch goats were determined from 768 brain tissue samples in 2005, 766 in 2008 and 300 in 2012, derived from random sampling for the national scrapie surveillance without knowledge of the breed. Breed specific frequencies were determined in the winter 2013/2014 by sampling 300 breeding animals from the main breeders of the different breeds. Detailed analysis of the scrapie‐resistant K222 haplotype was carried out in 2014 for 220 Dutch Toggenburger goats and in 2015 for 942 goats from the Saanen derived White Goat breed. Nine haplotypes were identified in the Dutch breeds. Frequencies for non‐wild type haplotypes were generally low. Exception was the K222 haplotype in the Dutch Toggenburger (29%) and the S146 haplotype in the Nubian and Boer breeds (respectively 7 and 31%). The frequency of the K222 haplotype in the Toggenburger was higher than for any other breed reported in literature, while for the White Goat breed it was with 3.1% similar to frequencies of other Saanen or Saanen derived breeds. Further evidence was found for the existence of two M142 haplotypes, M142 /S240 and M142 /P240 . Breeds vary in haplotype frequencies but frequencies of resistant genotypes are generally low and consequently selective breeding for scrapie resistance can only be slow but will benefit from animals identified in this study. The unexpectedly high frequency of the K222 haplotype in the Dutch Toggenburger underlines the need for conservation of rare breeds in order to conserve genetic diversity rare or absent in other breeds.